On the Beneficial Impact of Li2CO3 as Electrolyte Additive in NCM523 ∥ Graphite Lithium Ion Cells Under High‐Voltage Conditions. Issue 10 (25th January 2021) - Klein, Sven; Harte, Patrick; Henschel, Jonas; Bärmann, Peer; Borzutzki, Kristina; Beuse, Thomas; van Wickeren, Stefan; Heidrich, Bastian; Kasnatscheew, Johannes; Nowak, Sascha; Winter, Martin; Placke, Tobias
Abstract: Lithium ion battery cells operating at high‐voltage typically suffer from severe capacity fading, known as 'rollover' failure. Here, the beneficial impact of Li2 CO3 as an electrolyte additive for state‐of‐the‐art carbonate‐based electrolytes, which significantly improves the cycling performance of NCM523 ∥ graphite full‐cells operated at 4.5 V is elucidated. LIB cells using the electrolyte stored at 20 °C (with or without Li2 CO3 additive) suffer from severe capacity decay due to parasitic transition metal (TM) dissolution/deposition and subsequent Li metal dendrite growth on graphite. In contrast, NCM523 ∥ graphite cells using the Li2 CO3 ‐containing electrolyte stored at 40 °C display significantly improved capacity retention. The underlying mechanism is successfully elucidated: The rollover failure is inhibited, as Li2 CO3 reacts with LiPF6 at 40 °C to in situ form lithium difluorophosphate, and its decomposition products in turn act as 'scavenging' agents for TMs (Ni and Co), thus preventing TM deposition and Li metal formation on graphite. Abstract : The high‐voltage operation of NCM || graphite lithium ion cells is a serious challenge and results in severe capacity fading, due to transition metal (Ni, Co, Mn) dissolution from the cathode and deposition at the anode, subsequently inducing Li metal dendrite formation. This failure can be inhibited by suitable electrolyte additives, acting as 'scavenging' agents for transition metals.